Pengaruh Pemberian Aromaterapi Lavender Melalui Humidifier Terhadap Kualitas Tidur Pasien Kanker Payudara Di Murni Teguh Memorial Hospital - Rini Selviana Telaumbanua; Mhd. Taufik Daniel Hasibuan (PT. Hasba Edukasi Mandiri, 2025)
Chemotherapy is to anticipate, prevent and reduce patient suffering and wherever possible improve the quality of life of patients and their families, regardless of the stage of the disease or the need for other therapies. Sleep disorders can exist independently or in conjunction with other medical and psychiatric disorders, such as chronic pain and depression. The type of research used was the Pre-experimental design and used the Pre Test – Post Test Design method, using the Saturated Sampling technique with 27 respondents. Data collection using the PSQI questionnaire. Data was taken before and after the intervention was given and then statistically processed using the Wilcoxson test. The results of the study according to the characteristics of the majority were female, most respondents were aged 26-45 years (56%), most respondents had elementary school education (33%) and high school/vocational school (30%), with the majority being housewives (74%) . The results of research on sleep quality before and after being given the intervention showed an average score of 0.896 and 0.601. The Effect of Giving Lavender Aromatherapy Through Humidifire on the Sleep Quality of Breast Cancer Patients at Murni Teguh Memorial Hospital with a p-value = 0.000 which is said to have an effect if the p-value < α (0.05). It is hoped that future researchers can continue this research with the same or different interventions.